Arginine methylation of the cellular nucleic acid binding protein does not affect its subcellular localization but impedes RNA binding. Issue 9 (12th April 2014) - Wei, Hung-Ming; Hu, Huan-Hsuan; Chang, Gia-Yun; Lee, Yu-Jen; Li, Yi-Chen; Chang, Hong-How; Li, Chuan
Abstract : CNBP physically interacts with PRMT1 by anti tag coimmunoprecipitation (View interaction) Abstract : R25 or R27 appear to be the major methylation sites in CNBP. The RG motif or arginine methylation of CNBP do not affect its subcellular localization. Arginine methylation of CNBP impedes RNA binding.